Integration of Blockchain for Electronic Contract Proof Systems and Civil Law Review - Limbong, Riswan; Tamba, RL. Harmady; Siregar, Kristian (Judge : Jurnal Hukum, 2025)
The advancement of blockchain technology has opened new possibilities in strengthening the validity and security of electronic contracts. In an era where digital transactions are increasingly prevalent, the need for trustworthy and tamper-proof legal documentation has become critical. Blockchain, with its decentralized, immutable, and time-stamped ledger system, presents a promising solution for enhancing the proof mechanism of electronic contracts. However, in Indonesia, despite the legal recognition of electronic contracts under the Information and Electronic Transactions Law (ITE Law), there remains a gap in regulatory clarity regarding the legal force and admissibility of blockchain-based contracts in civil law proceedings. This study aims to explore the integration of blockchain technology into electronic contract systems and analyze its legal implications based on Indonesian civil law. The research employs a normative juridical approach, supported by technological analysis of blockchain infrastructure and smart contracts. Findings suggest that blockchain can fulfill several legal criteria for evidence, such as authenticity, integrity, and transparency. Nevertheless, the absence of explicit legal frameworks poses challenges to its enforceability, particularly in dispute resolution. The study concludes that while blockchain offers substantial benefits for securing electronic contracts, legal adaptation is necessary to fully recognize its potential within civil law contexts. It recommends the development of regulatory guidelines and legal standards to accommodate emerging technologies like blockchain, ensuring legal certainty, protection for contracting parties, and the integrity of digital agreements in Indonesia’s legal system.